Controlled synthesis of the antiperovskite oxide superconductor Sr3−xSnO. (11th April 2018) - Hausmann, J N; Oudah, M; Ikeda, A; Yonezawa, S; Maeno, Y
Abstract: A large variety of perovskite oxide superconductors are known, including some of the most prominent high-temperature and unconventional superconductors. However, superconductivity among the oxidation state inverted material class, the antiperovskite oxides, was recently reported for the first time. In this superconductor, Sr3− x SnO, the unconventional ionic state Sn 4− is realized and possible unconventional superconductivity due to a band inversion has been discussed. Here, we discuss an improved facile synthesis method, making it possible to control the strontium deficiency in Sr3− x SnO. Additionally, a synthesis method above the melting point of Sr3 SnO is presented. We show temperature dependence of magnetization and electrical resistivity for superconducting strontium deficient Sr3− x SnO ( T c  ∼ 5 K) and for Sr3 SnO without a superconducting transition in alternating current susceptibility down to 0.15 K. Further, we reveal a significant effect of strontium raw material purity on the superconductivity and achieve substantially increased M / M Meissner (∼1) compared to the highest value reported so far. More detailed characterizations utilizing powder x-ray diffraction and energy-dispersive x-ray spectroscopy show that a minor cubic phase, previously suggested to be another Sr3− x SnO phase with a slightly larger lattice parameter, is SrO. The improved characterization and controlled synthesis reported herein enable detailed investigations on the superconducting nature and its dependency on the strontium deficiency in Sr3− x SnO.